2006
DOI: 10.1055/s-2006-947201
|View full text |Cite
|
Sign up to set email alerts
|

Gigantol Isolated from the Whole Plants ofCymbidium goeringiiInhibits the LPS-Induced iNOS and COX-2 Expression via NF-κB Inactivation in RAW 264.7 Macrophages Cells

Abstract: During our efforts to find bioactive natural products with anti-inflammatory activity, we isolated gigantol from the whole plants of Cymbidium goeringii (Orchidaceae) by activity-guided chromatographic fractionation. Gigantol was found to have potent inhibitory effects on LPS-induced nitric oxide (NO) and prostaglandin E (2) (PGE (2)) production in RAW 264.7 cells. Consistent with these findings, gigantol suppressed the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) at the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…No concentration-dependent inhibitory effect was observed to allow IC 50 calculation for gigantol ( 3 ) effect on PGE-2 production. Wong JH et al also demonstrated that this compound ( 3 ) was able to reduce NF-κB expression on murine macrophages RAW 264.7 [38]. Thus, this transcriptor factor could be another target, leading to a reduction of PGE-2 synthesis and to a global anti-inflammatory effect on irradiated HaCaT.…”
Section: Resultsmentioning
confidence: 96%
“…No concentration-dependent inhibitory effect was observed to allow IC 50 calculation for gigantol ( 3 ) effect on PGE-2 production. Wong JH et al also demonstrated that this compound ( 3 ) was able to reduce NF-κB expression on murine macrophages RAW 264.7 [38]. Thus, this transcriptor factor could be another target, leading to a reduction of PGE-2 synthesis and to a global anti-inflammatory effect on irradiated HaCaT.…”
Section: Resultsmentioning
confidence: 96%
“…There are growing evidences that several agents inhibiting NO production have been shown to suppress NF-κB activation [34-37]. NF-κB regulates expression of various genes associated with apoptosis, proliferation, cancer progression and inflammation [38].…”
Section: Discussionmentioning
confidence: 99%
“…They have been used variously in different diseases as anti rheumatic, antiinflammatory, antiviral, anti carcinogenic, anticonvulsive, diuretic, neuroprotective, relaxation, anti-aging, wound healing, hypoglycemic, antitumor and anticancer, antimicrobial, antiviral and many other activities (Ghanaksh and Kaushik, 1999;Shyur et al, 2004;Li et al, 2001;Shimura et al, 2007;Wang et al, 2006;Prasad and Achari, 1966;Kumar et al, 2000;Zhao et al, 2003;Satish et al, 2003;Watanabe et al, 2007, Won et al, 2006Lawler and Slaytor, 1970;Balzarini et al, 1992;Nayak et al, 2005;Miyazawa et al, 1999). For drugs derived from orchids, some novel discoveries, both in phytochemical and pharmacological properties, were reported by some researcher.…”
Section: Orchids As a Rich Source Of Natural Compounds And Their Pharmentioning
confidence: 99%